Control measures for a recent invasion of Hieracium pilosella in Southern Patagonian rangelands - Cipriotti, Pablo Ariel (2012)
Plant invasions have important ecological impacts on biodiversity, the functioning of ecosystems and economic sustainability. In this study, we evaluated the effects of four control measures (pasture sown + fertiliser, fertiliser and selective/non-selective herbicide applications) in two different grazing conditions (grazed and ungrazed) during a recent invasion of the exotic herb Hieracium pilosella in northern grasslands of Tierra del Fuego Island in Southern Patagonia, Argentina. As response variables, we measured the cover of the invasive species, the dominant growth forms of other plant species, litter and bare soil at patch scales (m²) during two consecutive growing seasons. The effects of fertilisation depended on the grazing conditions; H. pilosella cover decreased by more than 92% and was replaced by dicotyledonous herbs in the ungrazed/fertilised subplots, while it exhibited no decrease in the grazed/fertilised subplots after the second growing season. Both herbicides (selective and non-selective) reduced H. pilosella cover by c. 63% compared with the untreated subplots independently of grazing. However, the non-selective herbicide application resulted in an increase in bare soil and litter cover in the treated grazed and ungrazed subplots respectively. In contrast, such effects were not observed with the selective broad-leaved herbicide application. A control strategy based on the local application of selective herbicides and/or NP fertilisers, in conjunction with a transient ban on sheep grazing, reduced the invader’s cover in the short term and at a local scale and also reduced the cover of bare soil through the restoration of native vegetation. An economic assessment of this strategy supported the profitability of these control measures.